Analisis psikologi hierarki kebutuhan tokoh utama dalam novel “Anak Rantau” karya Ahmad Fuadi: Pendekatan sosiologi sastra Abraham Maslow - Amboy, Abdul Givari Pratama (Maliki Interdisciplinary Journal, 2024)
Literary works are the result of observations made by writers based on the realities of society and their surrounding environment, as well as their own imagination. In the context of literary psychology, these works are essential for research because they allow for a deeper understanding of the psychological aspects of the characters within them. One relevant theory is Abraham Maslow’s hierarchy of needs theory. In the novel “Anak Rantau,” Ahmad Fuadi portrays the journey of an individual through their life experiences as a migrant. The social analysis approach using the concept of psychological hierarchy of needs enables us to explore the social dimensions of the main character’s life. We can detail the roles and influences of human needs according to Maslow’s hierarchy. This analysis aims not only to understand the dynamics of the character but also to uncover the hidden social and psychological meanings behind each action and event in the novel. By applying the psychology of hierarchical needs, we can dissect the main character’s interactions with their environment, examine their social roles, and observe the impact of their migration on the existing social structure. The main character is not just an individual but also part of a community with specific norms and values. This social analysis context provides an opportunity to understand how social needs, recognition, and self-actualization are reflected in the main character’s relationships with society. Utilizing Maslow’s hierarchy of needs theory, the author delves deeper into how the main character fulfills or struggles with these needs. In incorporating Maslow’s theory, the author draws upon concepts found in Maslow’s original work, such as “Human Motivation” and the “Hierarchy of Needs".